Achieving COVID‐19 herd immunity in Ethiopia - Bezawit Kassahun Bekele; Abdulbasit Opeyemi Muili; Iyaketing Akpan Udom; Lizeth Hernández‐Rubio; Yidnekachew Girma Mogessie; Shewit Yehuala Wubneh; Goodness Ogeyi Odey; Dawit Tesfagiorgis Mengesha (Wiley, 2023)
Abstract COVID‐19 has greatly impacted the society and economy of Ethiopia, with a total of 499,493 cases confirmed and a death toll of 7572 as of February 2023. The country began COVID‐19 vaccination in March 2021 and delivered about 52 million doses as of July 2022. The government liaised with the COVAX (COVID‐19 Vaccines Global Access) facility, the African Vaccine Acquisition Trust, and other donors to acquire the vaccine doses. However, in July 2022, Ethiopia achieved only 45 persons per 100 population coverage when the global average of doses administered was 167 per 100 population. These figures grossly fall behind the requirements for achieving herd immunity. The major challenges noted are vaccine hesitancy ranging from 14.1% to 68.7%, including that among healthcare workers (HCW). There was a lack of physical infrastructure and personnel to distribute the vaccines and to administer the doses to populations who had challenges accessing healthcare services. There was heavy disinformation regarding COVID‐19 vaccines. The various government ministries including the Ministry of Health (one government approach) and the regional and zonal health offices should coordinate for efficient and equitable vaccine distribution and build community trust by working with village leaders, religious groups, and media outlets. There is a need to continue efforts on providing an awareness of the importance of COVID‐19 vaccination and herd immunity. We review and dissect the COVID‐19 vaccination efforts in Ethiopia and provide recommendations for tackling these challenges, including equity in the distribution of vaccines and proper awareness of the disease to achieve herd immunity.